Copper: from neurotransmission to neuroproteostasis - Opazo, Carlos M.; Greenough, Mark A.; Bush, Ashley I. (Frontiers in Aging Neuroscience, 2014)
Copper is critical for the Central Nervous System (CNS) development and function. In particular, different studies have shown the effect of copper at brain synapses, where it inhibits Long Term Potentation (LTP) and receptor pharmacology. Paradoxically, according to recent studies copper is required for a normal LTP response. Copper is released at the synaptic cleft, where it blocks glutamate receptors, which explain its blocking effects on excitatory neurotransmission. Our results indicate that copper also enhances neurotransmission through the accumulation of PSD95 protein, which increase the levels of AMPA receptors located at the plasma membrane of the post-synaptic density. Thus, our findings represent a novel mechanism for the action of copper, which may have implications for the neurophysiology and neuropathology of the CNS. These data indicate that synaptic configuration is sensitive to transient changes in transition metal homeostasis. Our results suggest that copper increases GluA1 subunit levels of the AMPA receptor through the anchorage of AMPA receptors to the plasma membrane as a result of PSD-95 accumulation. Here, we will review the role of copper on neurotransmission of CNS neurons. In addition, we will discuss the potential mechanisms by which copper could modulate neuronal proteostasis (“neuroproteostasis”) in the CNS with focus in the Ubiquitin Proteasome System, which is particularly relevant to neurological disorders such Alzheimer’s disease (AD) where copper and protein dyshomeostasis may contribute to neurodegeneration. An understanding of these mechanisms may ultimately lead to the development of novel therapeutic approaches to control metal and synaptic alterations observed in AD patients.